Effect of alkali treatment on physical–chemical properties of sisal fibers and adhesion towards cement-based matrices. (22nd August 2022) - Castoldi, Raylane de Souza; de Souza, Lourdes Maria Silva; Souto, Felipe; Liebscher, Marco; Mechtcherine, Viktor; de Andrade Silva, Flávio
Highlights: Alkali treatment improves the mechanical performance of sisal fibers. Stretch of the fibers during treatment procedure results in enhanced fiber strength. Treated sisal fibers present an improved bond with cement-based matrix. Alkali-treated sisal fibers are more stable in alkaline aggressive conditions. Abstract: This work aims to evaluate the effect of alkali treatment on sisal fibers to improve the fiber properties and the effectiveness of their use as reinforcement in cement-based matrices. Alkaline solution concentration (1, 5 and 10 wt% NaOH) and post-treatment protocol (use of distilled water or acetic acid) influence were evaluated. The physical, chemical, thermal, wettability and surface characteristics were analyzed. Also, single-fiber direct tensile and pullout tests were performed. Results showed an increase in cellulose proportion with a reduction in hemicellulose and lignin content upon alkali treatment. Consequently, enhanced thermal stability and a decrease on the water uptake tendency were reached. Additionally, improved tensile properties, as well as an enhanced bond with the cementitious matrix, were found for alkali-treated fibers. Also, fibers became more stable when subjected to alkaline aggressive conditions. Thus, the alkali-treated sisal fiber seems to be an adequate and sustainable alternative as reinforcement for cement-based matrices.